2006
DOI: 10.1074/jbc.m607266200
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CXCL12 Induces Binding of Ferritin Heavy Chain to the Chemokine Receptor CXCR4, Alters CXCR4 Signaling, and Induces Phosphorylation and Nuclear Translocation of Ferritin Heavy Chain

Abstract: Chemokine receptor-initiated signaling plays critical roles in cell differentiation, proliferation, and migration. However, the regulation of chemokine receptor signaling under physiological and pathological conditions is not fully understood. In the present study, we demonstrate that the CXC chemokine receptor 4 (CXCR4) formed a complex with ferritin heavy chain (FHC) in a ligand-dependent manner. Our in vitro binding assays revealed that purified FHC associated with both the glutathione S-transferase-conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
112
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 58 publications
(38 reference statements)
1
112
0
1
Order By: Relevance
“…A recent study found several proteins, including ferritin (19) and Hsc73 (20), in combination with CXCR4 after internalization of CXCR4. The ferritin heavy chain and Hsc73 are not only found as CXCR4 binding proteins but also regulate the receptor endocytosis and the receptor-mediated chemotaxis (19,20). It has also been reported that ß-arrestin may regulate the internalization of CXCR4 (22).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study found several proteins, including ferritin (19) and Hsc73 (20), in combination with CXCR4 after internalization of CXCR4. The ferritin heavy chain and Hsc73 are not only found as CXCR4 binding proteins but also regulate the receptor endocytosis and the receptor-mediated chemotaxis (19,20). It has also been reported that ß-arrestin may regulate the internalization of CXCR4 (22).…”
Section: Introductionmentioning
confidence: 95%
“…Internalization of CXCR4 after SDF-1 treatment involves interaction with the proteins ferritin (19), 73-kDa heat shock cognate protein (Hsc73) (20), plectin (10) and Myosin IIA (21). A recent study found several proteins, including ferritin (19) and Hsc73 (20), in combination with CXCR4 after internalization of CXCR4.…”
Section: Introductionmentioning
confidence: 99%
“…The third receptor involves the CXCL12 chemokines and their receprtors. It has been shown that H-subunit rich ferritins can repress chemokine receptor-mediated signal transduction and migration of lymphocytes by binding to the CXCL12 chemokine's receptor (Li et al, 2006). The CXCL12 chemokines have chemotactic and various activating effects that play important roles in T-helper cell responses.…”
Section: Immune Modulation By Secreted H-subunit Rich Ferritinsmentioning
confidence: 99%
“…On the inside of the cell the H-subunit rich ferritins are phosphorylated followed by nuclear translocation. Furthermore, intracellular H-subunit rich ferritins can repress CXCR4 activation followed by inhibition of lymphocyte migration (Li et al, 2006). Most of the immunomodulatory studies involving H-subunit rich ferritins seem to be of an anti-inflammatory nature.…”
Section: Immune Modulation By Secreted H-subunit Rich Ferritinsmentioning
confidence: 99%
“…Thus, the major function of FTH1 is protecting the cell from oxidative damage (11). Recent data indicated that the FTH1 gene is also associated with several disease processes, such as inflammation, tumor progression, and so on (12,13).…”
Section: Introductionmentioning
confidence: 99%